The effectiveness of dual-magnetic controlled growth rods in the distraction period in the treatment of early-onset scoliosis (Annals of Medical Research, 2021)
Aim: The aim of the present study is to evaluate our dual magnetic controlled growing rod practices in early-onset scoliosis in terms of curve correction and control, and the effect on sagittal and coronal balance until definitive fusion surgery.Material and Methods: Ten patients under 10 years of age who had a major curvature of more than 30 degrees with the diagnosis of early-onset scoliosis and were operated on between 2014-2018 were included in the study. The mean age of the patients was 8.8 years (range, 7-10) and the mean follow-up was 26 months (range, 12-36). Magnetic rod was distracted at between 12-week intervals with a mean distraction per patient of 8.2 times (range, 6-12). Cobb angle, T1-T12 kyphosis angle, T1-S1 lengths, the coronal and sagittal balance were all evaluated.Results: The mean pre-operative, post-operative and last follow-up Cobb angle results were 54°±16 (range, 40-88), 28°±14 (range, 10-55) and 30°±16 (range, 10-59), respectively (p0.05). The mean pre-operative, post-operative and last follow-up T1-S1 lengths were 276 ± 53 mm (range, 170-365), 309±49 mm (range, 207-385) and 348±55 mm (range, 227-405), respectively (p0.05). The mean pre-operative, post-operative and last follow-up kyphosis angle was 49°±18 (range, 21-74), 22°±8 (range, 10-39) and 21°±5 (range, 12-28), respectively (p0.05). No complications were observed during the operation, outpatient distraction and at the last follow-up. Conclusion: In our short-term follow-up, the dual-magnetic rod technique allowed the spinal growth and control of scoliosis and lengthening.